The Attitude of Budapest to the Election of the President of the Republic in Czechoslovakia in December 1935 - Tóth, Andrej (Univerzita Karlova, Filozofická fakulta, 2015)
The study describes the attitude of Budapest to the election of the President of the Republic in Czechoslovakia in December 1935, electing the successor to Tomáš Garrigue Masaryk, the first President of the Czechoslovak Republic who had been in office long years. The election of the President of the Czechoslovak Republic in late 1935 was the first presidential election with active participation of the opposition and negativistic Hungarian minority legislators of the Czechoslovak National Assembly from both Hungarian minority parliamentary parties, the Land Christian-Socialist Party (OKSzP) and the Hungarian National Party (MNP) who had always cast empty votes in presidential elections until that time, to declare their negativistic attitude to the constitutional limits of the Czech Republic. In 1935, they even supported the presidential candidate Edvard Beneš, the Foreign Minister to whom the Hungarian minority political representation including the very Budapest had a very negative attitude as he had been one of the main architects of the Versailles rearrangement of Central Europe after World War I, refused by the Hungarians, as the Hungarian state had lost two thirds of its territory and about seven hundred and fifty thousand Hungarians landed in Czechoslovakia in position of national and non-state-constituting minority due to it. But in spite of that fact, the Hungarian minority legislators from OKSzP and MNP, with political support of Budapest, sided with Benešʼs candidacy; thus the Hungarian minority was the only one out of the two large negativistic national minorities of the Czechoslovak Republic of that time, besides the minority Germans whose representatives in the Czechoslovak Parliament, on behalf of the opposition and negativistic OKSzP and MNP parties took an activistic attitude, increasing the national-political and the foreign-political prestige of Edvard Benešʼs presidential mandate.
Postoj Budapešti k volbě prezidenta republiky v Československu v prosinci 1938
Keywords: History; 20th century; Politics; Czechoslovakia; Hungary; Presidential election; 1935; Edvard Beneš; János Esterházy; Géza Szüllő; Andor Jaross; Kálmán Kánya; Historie; 20. století; politika; Československo; Maďarsko; prezidentská volba; 1935; Edvard Beneš; Géza Szüllő; Andor Jaross; Kálmán Kánya